Regeneration of dentin–pulp-like tissue using an injectable tissue engineering technique. Issue 73 (9th August 2015) - Tan, Linhua; Wang, Jun; Yin, Shuo; Zhu, Wenting; Zhou, Guangdong; Cao, Yilin; Cen, Lian
<x xml:space="preserve">Abstract</x> An injectable tissue engineering technique to regenerate dentin–pulp complex.